El crecimiento económico y los factores endógenos de las regiones del Perú 2015 – 2019 - Peralta Romero, Katty Judith (2022)
The aim of this research was to determine how endogenous factors influence economic growth in the regions of Peru, for the period 2015-2019, through a descriptive analysis and an econometric model of panel data with fixed effects. It used annual data from all regions of Peru, extracted from the Peruvian Institute of Economics (IPE), the National Institute of Statistics and Informatics (INEI), and the National Council for Science, Technology and Innovation (CONCYTEC). The evolution of economic growth was analysed, and the influence of the following variables on it, where the number of researchers, patent applications and the economically active population employed with at least advanced education showed a degree of influence of 0.16%, 0.19% and 0.20%, respectively, on economic growth. It was concluded that the endogenous factors of the regions of Peru influence economic growth, the influence is direct on the 3 variables in a proportional manner; however, a problem was found reflected in the study on the centralisation that exists in Lima region.